Tumour mutational burden: clinical utility, challenges and emerging improvements - Budczies, Jan; Kazdal, Daniel; Menzel, Michael; Beck, Susanne; Kluck, Klaus; Altbürger, Christian; Schwab, Constantin; Allgäuer, Michael; Ahadova, Aysel; Kloor, Matthias; Schirmacher, Peter; Peters, Solange; et al. (Nature reviews. Clinical oncology, 2024)
Tumour mutational burden (TMB), defined as the total number of somatic non-synonymous mutations present within the cancer genome, varies across and within cancer types. A first wave of retrospective and prospective research identified TMB as a predictive biomarker of response to immune-checkpoint inhibitors and culminated in the disease-agnostic approval of pembrolizumab for patients with TMB-high tumours based on data from the Keynote-158 trial. Although the applicability of outcomes from this trial to all cancer types and the optimal thresholds for TMB are yet to be ascertained, research into TMB is advancing along three principal avenues: enhancement of TMB assessments through rigorous quality control measures within the laboratory process, including the mitigation of confounding factors such as limited panel scope and low tumour purity; refinement of the traditional TMB framework through the incorporation of innovative concepts such as clonal, persistent or HLA-corrected TMB, tumour neoantigen load and mutational signatures; and integration of TMB with established and emerging biomarkers such as PD-L1 expression, microsatellite instability, immune gene expression profiles and the tumour immune contexture. Given its pivotal functions in both the pathogenesis of cancer and the ability of the immune system to recognize tumours, a profound comprehension of the foundational principles and the continued evolution of TMB are of paramount relevance for the field of oncology.
Zuerst veröffentlicht: 27. August 2024
Gesehen am 15.10.2024